1987
DOI: 10.1111/j.1471-0528.1987.tb03150.x
|View full text |Cite
|
Sign up to set email alerts
|

Control of menorrhagia by the cyclo‐oxygenase inhibitors naproxen sodium and mefenamic acid

Abstract: Summary Thirty‐five patients with menorrhagia were treated in a double‐blind crossover study with naproxen sodium and mefenamic acid after measurement of their blood loss during control menstrual cycles. Treatment with these compounds reduced the excessive bleeding by an average of 46 and 47% respectively. Drugs in the prostaglandin synthetase inhibitor group are considered to have an important place in the treatment of menorrhagia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(19 citation statements)
references
References 11 publications
(6 reference statements)
1
17
0
1
Order By: Relevance
“…In a previous study we found that mefenamic acid reduced the mean menstrual loss by 20% compared with 60% with danazol over two consecutive menstrual periods; adverse side effects were significantly more common with danazol (75% of patients) than with mefenamic acid (30%) 17. The percentage reduction in menstrual blood loss reported with mefenamic acid is usually in the range 20-35%,11 18 19 though reductions of up to 46% have been reported 20…”
Section: Discussionmentioning
confidence: 91%
“…In a previous study we found that mefenamic acid reduced the mean menstrual loss by 20% compared with 60% with danazol over two consecutive menstrual periods; adverse side effects were significantly more common with danazol (75% of patients) than with mefenamic acid (30%) 17. The percentage reduction in menstrual blood loss reported with mefenamic acid is usually in the range 20-35%,11 18 19 though reductions of up to 46% have been reported 20…”
Section: Discussionmentioning
confidence: 91%
“…Seventeen of these studies required that patients objectively lose greater than 80 milliliters menstrual blood loss per cycle in order to be eligible for study participation. [10-15, 18-23, 25-29] Five studies included a levonorgestrel intrauterine system arm [15, 20, 22, 26, 27], 5 studies included a OCP arm [15, 16, 21, 27, 29], 5 studies included a luteal progestin arm[8, 11, 19, 22, 25], 1 study included an extended oral progestin arm[20], 8 studies included an NSAID arm[9, 11-13, 16-18, 36], 7 studies included an antifibrinolytic arm (tranexamic acid, tranexamic acid prodrug, or epsilon amino caproic acid) [9, 10, 14, 23-25, 28]. Studies ranged in quality, and the quality of individual studies are noted in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…All but one [8, 34]calculated the change in menstrual blood loss quantitatively using the objective alkaline-hematin method [18-23, 25-38] and/or the semi-objective pictorial blood assessment chart [15, 26, 27, 35]. Data are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…У плановому поряд-ку терапію НПЗП слід починати за день до менструації і продовжувати протягом 3-5 днів або до припинення кровотечі. Істотні відмінності ефективності між різними НПЗП не виявлені [7].…”
Section: негормональні методи лікування амкunclassified